A Study on Comparative Analysis Regarding Gen-Z’s Perception Over Domino’s Pizza and Pizza Hut in Ahmedabad City - Shah , Henil; Mehta, Pankti; Vidani, Jignesh (International Journal of Economic, Finance and Business Statistics, 2024)
This study investigates Generation Z's perceptions of Domino’s and Pizza Hut in Ahmedabad, focusing on factors such as food quality, pricing, and brand reputation. Utilizing a quantitative approach, the research tests eight hypotheses related to the influence of age on these perceptions. The findings reveal that age does not significantly impact how Generation Z evaluates these brands, leading to the rejection of all null hypotheses. This suggests a shared perspective among this demographic, indicating that factors beyond age—such as overall experience and brand engagement—are crucial in shaping their preferences. The study highlights the need for targeted marketing strategies that resonate with Generation Z's values, particularly in terms of health, sustainability, and digital engagement. Furthermore, enhancing customer experiences and effectively communicating brand value are essential for building loyalty. The findings also emphasize the importance of corporate social responsibility initiatives in improving brand reputation among socially conscious consumers. The study concludes by offering recommendations for future research, including broader demographic analyses and qualitative approaches to gain deeper insights into consumer motivations.